Nonlinear dynamic modelling of flexible beam structures using neural networks - Mohd. Hashim, Siti Zaiton (IEEE, 2004)
This paper investigates the utilisution of back propagation neural networlu (NNs) for modelling flexible beam structures infixed-free mode; a simple repsentation of an aircrufr wing or robot arm. A comparative performance of the NN model and conventional recursive least square scheme, in characterising the system is carried out in the time and frequency domains. Simulated results demonstrate that using NN approach the system is modelled better than with the conventional linear modelling approach. The developed neuro-modelling approach will firther be utilized in the design and implementation of suitable controllers, for vibration slippression in such system.